2018
DOI: 10.1038/s41598-017-19113-z
|View full text |Cite|
|
Sign up to set email alerts
|

Visual field loss and vision-related quality of life in the Italian Primary Open Angle Glaucoma Study

Abstract: The aim of this study was to examine the relationship between visual field (VF) loss, vision-related quality of life (QoL) and glaucoma-related symptoms in a large cohort of primary open angle glaucoma (POAG) patients. POAG patients with or without VF defects or “glaucoma suspect” patients were considered eligible. QoL was assessed using the validated versions of the 25-item National Eye Institute Visual Function Questionnaire (NEI-VFQ-25) and glaucoma-related symptoms were assessed using the Glaucoma Symptom … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 80 publications
0
30
1
9
Order By: Relevance
“…[ 25 , 26 ] It was reported that the QOL in glaucoma was significantly correlated with visual impairment of physical function, social activities and psychosocial factors, [ 27 30 ] among which binocular visual function has the most intimate relationship. [ 31 , 32 ] In addition, once glaucoma is diagnosed, many patients’ QOL decreases significantly, mainly due to inconvenient treatment and afraid of blindness. [ 33 ] During clinical practice, patients with the same stage of VF defect showing various QOL, or same QOL demonstrate diverse severity of VF defect, which might not be explained by visual function assessment based on monocular VF loss.…”
Section: Discussionmentioning
confidence: 99%
“…[ 25 , 26 ] It was reported that the QOL in glaucoma was significantly correlated with visual impairment of physical function, social activities and psychosocial factors, [ 27 30 ] among which binocular visual function has the most intimate relationship. [ 31 , 32 ] In addition, once glaucoma is diagnosed, many patients’ QOL decreases significantly, mainly due to inconvenient treatment and afraid of blindness. [ 33 ] During clinical practice, patients with the same stage of VF defect showing various QOL, or same QOL demonstrate diverse severity of VF defect, which might not be explained by visual function assessment based on monocular VF loss.…”
Section: Discussionmentioning
confidence: 99%
“…The Secondary childhood glaucoma is classified into four categories: glaucoma associated with nonacquired ocular anomalies, glaucoma associated with nonacquired systemic anomalies, glaucoma associated with the acquired condition, and glaucoma following cataract surgery [29]. In children, the most common form is PCG, with a prevalence rate of 1:10,000 to 18,000 live births worldwide [30,31]. The frequency of CYP1B1 mutations in people with PCG depends on the population being considered.…”
Section: Cyp1b1 In Glaucomamentioning
confidence: 99%
“…Briefly, previously or newly diagnosed POAG patients aged 18 or more were consecutively enrolled during routine visits at 21 academic and non-academic centers in Italy. In the cross-sectional part of the study, vision-related QoL data were collected and their association with both clinical and socio-demographic variables was investigated 29,30 . In the prospective part of the study, consecutive newly-diagnosed glaucoma patients were evaluated at baseline and were followed-up for one year.…”
Section: Methodsmentioning
confidence: 99%